ZAKI NAGUIB MAHMOUD’S THOUGHT ON IDEAL POLITICS (From Social-Criticism to Liberating-Nationalism) - Supriyanto Supriyanto; Doromae Hayeehasa (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2021)
Political dynamics in Muslim countries experienced turbulence after the collapse of the Ottoman Empire. In the midst of uncertainty about model of Islamic politics in Muslim countries, sometimes they even deny each other, this has prompted the birth of an offer of Islamic political thought by the great Muslim thinker, Zaki Naguib Mahmoud. This study aims to reveal the ideal political model of Islam in the context of the contemporary nation state. The researcher examines Zaki's thinking as a representation of contemporary Muslim scholar who have a long scientific anchor in the Muslim tradition. This research is qualitative research with a discourse analysis method. As a result, Zaki offers a political concept that is not only oriented to the struggle for power, but a political concept that liberates, prospers, and always tries to build a better life order. Zaky is here to oppose the tyranny of power and the hegemony of the majority over the minority. For the Arabs, the realization of such a political vision is not impossible, considering that they have a noble heritage in the form of a spirit of nationalism rooted in the era of their predecessors. It is this spirit that should be able to create a political order capable of liberating the entire Arab nation from backwardness, decline, and moral degradation.